Influenza-Associated Encephalitis/Encephalopathy with a Reversible Lesion in the Splenium of the Corpus Callosum: A Case Report and Literature Review - Takanashi, Jun-ichi; Barkovich, A. James; Yamaguchi, Ken-ichi; Kohno, Yoichi (American journal of neuroradiology : AJNR, 2004)
We report the cases of two patients with influenza-associated encephalitis/encephalopathy (IAEE) who presented with mild CNS manifestations and complete recovery within a few days. Initial MR imaging at days 4 and 5 revealed a lesion in the central portion of the splenium of the corpus callosum with a reduced apparent diffusion coefficient (ADC) value, which completely resolved on follow-up studies at day 10. We postulate two possible mechanisms for decreased ADC; namely, intramyelinic edema and an inflammatory infiltrate.